The effect of peer feedback on EFL students' writing revision: A case study at Nam Yen high school - Cao Thị Diệu Nhi (Trường Đại học Trà Vinh, 2023)
The purpose of the study is to examine, in the specific context of Nam Yen high school, how students' incorporation of their peers' comments in comparison with teacher’s comments in order to see the feasibility of this method in the research context. In addition, the study wants to get a hold of students reactions when they receive feedback from both teacher and peers when they revise their drafts. Finally, the study aims to find out factors that can make it difficult for students when receiving feedback from their peers and giving feedback to others’ drafts.